2018
DOI: 10.1002/ps.5190
|View full text |Cite
|
Sign up to set email alerts
|

Fenoxaprop‐ethyl affects mouse oocyte quality and the underlying mechanisms

Abstract: Our results indicate that FE has adverse effects on oocyte quality as assessed by maturation and fertilization potential, due to disrupted cytoskeletal integrality, and mitochondrial dysfunction leading to ROS accumulation, apoptosis and autophagy. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…The results revealed that the serum TG and TC levels were significantly increased in the tumor-bearing group compared with in the control group, alongside the number of abnormal oocytes. The abnormal rate of oocytes of the tumor-bearing group (57.10%) was increased compared with that of the control group (41.90%), although the number of abnormal oocytes in the control group was higher than that in a previous report (39 abnormal oocytes out of 93 oocytes) (16), which may be associated with the batch deference of mice. It was previously reported that the growth and survival of tumor cells depended on lipid metabolism, as the lipids could provide the energy for the proliferation of tumor cells (17).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The results revealed that the serum TG and TC levels were significantly increased in the tumor-bearing group compared with in the control group, alongside the number of abnormal oocytes. The abnormal rate of oocytes of the tumor-bearing group (57.10%) was increased compared with that of the control group (41.90%), although the number of abnormal oocytes in the control group was higher than that in a previous report (39 abnormal oocytes out of 93 oocytes) (16), which may be associated with the batch deference of mice. It was previously reported that the growth and survival of tumor cells depended on lipid metabolism, as the lipids could provide the energy for the proliferation of tumor cells (17).…”
Section: Discussioncontrasting
confidence: 68%
“…3). The number of normal and abnormal oocytes was counted; the results revealed that there were 39 abnormal oocytes out of a total of 93 oocytes in the control group, which was higher than that of a previous study (16), while there were 36 abnormal oocytes out of a total of 63 oocytes in the tumor-bearing group (Table II). The abnormal rate of oocytes in the tumor-bearing group (57.10%) was increased compared with that in the control group (41.90%) (Table II).…”
Section: Effects Of S-180 Tumors On the Morphology Of The Ovaries Andmentioning
confidence: 57%
“…ROS levels in the oocytes were assessed in accordance with the manufacturer’s procedure [ 35 ]. MII oocytes subjected to different experimental conditions were incubated in α-MEM supplemented with 10 μM 2′,7′-dichlorodihydrofluorescein diacetate (Beyotime Institute of Biotechnology) at 37 °C for 30 min, then washed with PBS at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured using a rotary laser confocal microscope (Dragonfly, Andor Technology). Oocytes with green fluorescence on the cytoplasmic membrane were considered early apoptotic oocytes ( He et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The final step of oocyte development is oocyte maturation, which refers to when arrested oocytes resume meiosis and progress to metaphase II (MII). The process of oocyte maturation is particularly vulnerable to environmental pollutants and chemicals ( Rhind et al, 2010 ; He et al, 2019 ). The impairment of oocyte maturation may produce poor quality of oocytes, which is the common cause of infertility, miscarriage, and congenital genetic disease ( Nagaoka et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%